2020
DOI: 10.1111/rda.13617
|View full text |Cite
|
Sign up to set email alerts
|

Chicken seminal fluid lacks CD9‐ and CD44‐bearing extracellular vesicles

Abstract: The avian seminal fluid (SF) is a protein‐rich fluid, derived from the testis, the rudimentary epididymis and, finally, from the cloacal gland. The SF interacts with spermatozoa and the inner cell lining of the female genital tract, to modulate sperm functions and female immune responsiveness. Its complex proteome might either be free or linked to extracellular vesicles (EVs) as it is the case in mammals, where EVs depict the tetraspanin CD9; and where those EVs derived from the epididymis (epididymosomes) als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Our own studies using pig as model animal have shown that specific fractions of the ejaculate or even their sperm-free SP elicit dramatic modifications to the expression of genes related to sperm survival and function as well as to the immune status of the female’s various compartments of the internal genital tract—pre-ovulation [ 29 , 172 ] but even during early embryo development [ 173 ]. We have seen a similar set of results in chicken in response to mating, despite the uncertainty of the presence of similar types/amounts of EVs in roosters [ 170 ], implying the response might well be a conserved mechanism in animals with internal fertilization [ 3 ]. Since there is a mix of EVs shed by the prostate or the seminal vesicles (or even perhaps the bulbourethral glands) [ 76 , 169 , 174 , 175 ], pig SP EVs show heterogeneity in surface markers [ 39 , 40 , 140 ], probably because they also have a unique high level of cholesterol and sphingomyelin [ 143 ] and of lipoproteins (LDL/HDL) [ 40 ], which, by stabilizing the plasma membrane, could later aid in regulating sperm membrane fluidity before and during sperm capacitation [ 56 ].…”
Section: The Particulate Seminal Plasma: the Most Relevant Component Of Seminal Plasma?mentioning
confidence: 72%
See 1 more Smart Citation
“…Our own studies using pig as model animal have shown that specific fractions of the ejaculate or even their sperm-free SP elicit dramatic modifications to the expression of genes related to sperm survival and function as well as to the immune status of the female’s various compartments of the internal genital tract—pre-ovulation [ 29 , 172 ] but even during early embryo development [ 173 ]. We have seen a similar set of results in chicken in response to mating, despite the uncertainty of the presence of similar types/amounts of EVs in roosters [ 170 ], implying the response might well be a conserved mechanism in animals with internal fertilization [ 3 ]. Since there is a mix of EVs shed by the prostate or the seminal vesicles (or even perhaps the bulbourethral glands) [ 76 , 169 , 174 , 175 ], pig SP EVs show heterogeneity in surface markers [ 39 , 40 , 140 ], probably because they also have a unique high level of cholesterol and sphingomyelin [ 143 ] and of lipoproteins (LDL/HDL) [ 40 ], which, by stabilizing the plasma membrane, could later aid in regulating sperm membrane fluidity before and during sperm capacitation [ 56 ].…”
Section: The Particulate Seminal Plasma: the Most Relevant Component Of Seminal Plasma?mentioning
confidence: 72%
“…Obviously, epididymosomes can modify both ejaculated spermatozoa [ 40 , 75 ] and/or the influence the female genital tract [ 27 , 40 , 75 , 102 ]. In chickens, where a rudimentary epididymis is prevalent, we have not been successful in detecting relevant amounts of epididymosomes in seminal fluid, at least not using the same tetraspanin/CD44 markers we used in pigs [ 170 ]. In turn, a very recent study, using ultracentrifugation, the WB of the protein markers and EM has shown the presence of small EVs (possibly exosomes), in the seminal fluid of roosters with different fertility with capacity to putatively incorporate into spermatozoa [ 171 ].…”
Section: The Particulate Seminal Plasma: the Most Relevant Component Of Seminal Plasma?mentioning
confidence: 99%
“…SPEVs play a key role in sperm function and in establishing fertility, and in avians, there are few studies describing SPEVs. The earliest researchers believed that chicken seminal fluid lacks CD9 and CD44 bearing extracellular vesicles (Alvarez‐Rodriguez et al., 2020). The current accumulated studies indicate the presence of EVs with a classic bilayer membrane structure; particle size distributed 30–250nm and multiple marker proteins were identified (Chen et al., 2020); and the results were consistent with this study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Alvarez-Rodriguez et al [ 254 ] were not able to detect CD9 (or CD44) in chicken seminal plasma, and they observed no or rare extracellular vesicles, suggesting that interaction of avian seminal fluid with the female genital tract occurs in a manner distinct from that in mammals.…”
Section: Tetraspanins In Evs Of the Female And Male Reproductive Smentioning
confidence: 99%